Metode Istinbat Hukum Jaringan Islam Liberal (JIL) - Arif Susandi (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2009)
The methods of interpreting al-Qur’an often elaborate upon philosophy, lest, and reality and those give new perspectives towards some controversies in Islamic laws. This chapter explains about one method which is practiced by Islamic Liberal Network (JIL). Commonly JIL contributes the rational thought and it is based on the maslahah principles.